2009
DOI: 10.1371/journal.pgen.1000725
|View full text |Cite
|
Sign up to set email alerts
|

A Dominant Mutation in mediator of paramutation2, One of Three Second-Largest Subunits of a Plant-Specific RNA Polymerase, Disrupts Multiple siRNA Silencing Processes

Abstract: Paramutation involves homologous sequence communication that leads to meiotically heritable transcriptional silencing. We demonstrate that mop2 (mediator of paramutation2), which alters paramutation at multiple loci, encodes a gene similar to Arabidopsis NRPD2/E2, the second-largest subunit of plant-specific RNA polymerases IV and V. In Arabidopsis, Pol-IV and Pol-V play major roles in RNA–mediated silencing and a single second-largest subunit is shared between Pol-IV and Pol-V. Maize encodes three second-larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
171
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(183 citation statements)
references
References 86 publications
9
171
3
Order By: Relevance
“…Previous studies have shown that b1 repeat transcription is not altered in a mutation of mop2, which encodes the second largest subunit of a Pol IV/Pol V-related complex (27). This suggests that Pol II might be the major polymerase contributing to b1 repeat transcription.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Previous studies have shown that b1 repeat transcription is not altered in a mutation of mop2, which encodes the second largest subunit of a Pol IV/Pol V-related complex (27). This suggests that Pol II might be the major polymerase contributing to b1 repeat transcription.…”
Section: Resultsmentioning
confidence: 91%
“…Studies in Tetrahymena suggest RDRs can also interact directly with Dicer proteins (41) and that this interaction is required for siRNA biogenesis. Our observations that mop1 is required to maintain the silent state (5) but that b1TR-siRNAs are not required to maintain silencing of B′ (27) suggest that mop1 may have a function in maintaining B′ silencing beyond generating b1TR-siRNAs.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations